Pricing holder-extendable options in a stochastic volatility model with an Ornstein-Uhlenbeck process - Ibrahim, Siti Nur Iqmal; Ng, Teck Wee; O'Hara, John G.; Nawawi, A. (Institute for Mathematical Research, Universiti Putra Malaysia, 2017)
Holder-extendable options are characterized by two maturity dates, which means the option can be exercised at either the expiration date or the extended maturity date. This paper develops a pricing framework for holder-extendable options which deals with the extended version of a stochastic volatility model with an Ornstein-Uhlenbeck (OU) process. The extended model allows correlation between volatility and asset returns. The method uses Fourier inversion techniques that does not require an initial guess of the characteristic functions. A closed-form pricing formula for holder-extendable options is derived for logarithmic asset price dynamics.